Perry Bros and Robinson's combined circus and zoo. - Perry Bros. Circus; Robinsons Family Circus ([Australia] : Perry Bros Circus and Robinson Family Circus, 1989)
Poster promoting performances. Features nine black and white photographs of circus acts. A blank white panel appears at the foot. Text partly in red and partly in black.
Caption title.
Vivian James Carter Collection.
The original Perry Bros. Circus was founded over 100 years ago, when the Perry ancestors owned 'The Half-Way Hotel', between Tambo and Blackall in Western Queensland. They eventually exchanged the hotel for a bullock team and so started their circus days ... During the 1930s, Perrys became one of the biggest shows in Australia. They were particularly well known for their High-Jumping horses..."--from a Perry Bros. poster, vn 7326049. In 1976, Robert William Perry and his brother Albert (Alby) took over the business. In the 1980s, Mr Perry operated a three-ring show and attracted the talent of Tommy Hanlon. The Perry Bros Circus was sold to the Stardust Circus in 1993.
Steve and Linda Robinson founded Robinson's Family Circus in New Zealand in 1975, with its beginning in agricultural shows and shopping centres. Steve Robinson had worked with Perry Bros Circus before founding Robinsons' Family Circus. In 1989 Robinson Family Circus and Perry Bros Circus combined their shows in a short-lived tour of the QLD/NSW coast. The circus name was changed to Robinson Circus/Robinson International circus in the 90's. The original Robinson Circus closed down in 1997. Steve Robinson's son, Mark and his wife, Karlene, toured a new small scale Robinson Family Circus on the agricultural show circuit, until the end of 2013.
Keywords: Perry Bros. Circus -- Posters; Robinsons Family Circus -- Posters; Circus -- Australia -- Posters; Circus posters -- Australia; Advertising -- Circus -- Australia -- Posters; Amusements -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian